Pengembangan Pemasaran Digital Dan Desain Pengemasan Jamu Gendong Desa Rejoagung, Ploso, Jombang - Muhiddin, Muhiddin; Winarti, Winarti; Mumtaza, Abdurrahman; Muhibbuddin, Muhibbuddin (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2023)
Jamu Gendong is a traditional herbal beverage that has become an integral part of Indonesia's cultural heritage and ancestral knowledge. This dedication aims to develop effective digital marketing and packaging design for Jamu Gendong products in the village of Rejoagung. The method used, known as Assets Based Community Development (ABCD), involves a collaborative approach to community development, engaging researchers, local communities, and Jamu Gendong business practitioners. The implementation of more appealing digital marketing and packaging design is expected to enhance the product's competitiveness, expand the market, and provide positive impacts on the economy and culture of Rejoagung Village. This dedication has yielded significant advancements for Jamu Gendong sellers in terms of packaging design and marketing strategies, thus enabling market expansion and boosting the success of the Jamu Gendong business in Rejoagung Village.